Khwāmph̨̄očhai nai kānthamngān kh̨̄ong khrū, ʻāčhān nai rōngrīan lao sāi witthayākān sangkat K̨̄ongthap Bok - Mārisā Khunyotying (Phāk Wichā Ratthaprasāsanasāt, Čhulālongk̨̄onmahāwitthayālai, 1992)
Study on job satisfaction of vocational school teachers run by Royal Thai Army.